Additional effect of magnifying narrow‐band imaging on estimating the invasion depth of superficial esophageal cancer. Issue 2 (19th August 2019) - Kato, Minoru; Hayashi, Yoshito; Uema, Ryotaro; Kimura, Keiichi; Inoue, Takanori; Sakatani, Akihiko; Yoshii, Shunsuke; Tsujii, Yoshiki; Shinzaki, Shinichiro; Iijima, Hideki; Takehara, Tetsuo
Abstract : Background and Aim: To investigate whether assessment by magnifying narrow‐band imaging (M‐NBI) based on the classification of the Japan Esophageal Society provides additional value to the estimation of the invasion depth of superficial esophageal squamous cell carcinoma (SCC) compared with assessment by white light endoscopy (WLE) alone. Methods: Endoscopic images of 211 consecutive superficial esophageal SCCs resected by endoscopic submucosal dissection were separated into WLE and M‐NBI images. Depth estimation was performed independently by five evaluators using the numerical depth estimation scale (0 = epithelium (EP)/lamina propria (LPM), 1 = EP/LPM > muscularis mucosa (MM)/shallow submucosa (SM1), 2 = MM/SM1 > EP/LPM, 3 = MM/SM1, 4 = MM/SM1 > deep submucosa (SM2), 5 = SM2 > MM/SM1, 6 = SM2), using primarily WLE images (step 1), and subsequently both WLE and M‐NBI images (step 2). The discordance scores, determined by the average of the five evaluators' difference between the estimated score (from 0 to 6) and pathological score (0 for histologically proven EP/LPM, 3 for MM/SM1, and 6 for SM2), were analyzed in steps 1 and 2. Results: The discordance scores significantly decreased in step 2 (0.53 ± 0.06) compared with those in step 1 (0.79 ± 0.07) ( P  < 0.001). When the discordance score < 1.5 was regarded as a clinically correct diagnosis, the rate of the clinically correct diagnosis significantly increased in step 2 compared with that in step 1 (81% to 91%, P  < 0.001). Conclusion: M‐NBI has an additive value for estimating the invasion depth of superficial esophageal SCCs. Abstract : Depth estimation of 211 superficial esophageal squamous cell carcinomas (SCCs) (171 epithelial [EP] or lamina propria [LPM] cancers, 31 muscularis mucosa [MM] or shallow submucosal [SM1] cancers, and 9 deep submucosal [SM2] cancers) was performed independently by five evaluators (A, B, C, D, and E) using the numerical depth estimation scale (0 = EP/LPM, 1 = EP/LPM > MM/SM1, 2 = MM/SM1 > EP/LPM, 3 = MM/SM1, 4 = MM/SM1 > SM2, 5 = SM2 > MM/SM1, 6 = SM2), using primarily white light endoscopy (WLE) images (step 1) and, subsequently, both WLE and magnifying narrow‐band imaging (M‐NBI) images (step 2). The mean difference between the estimated score (from 0 to 6) and pathological score (0 for histologically proven EP/LPM, 3 for MM/SM1, and 6 for SM2) was significantly decreased in step 2 compared with that in step 1 for all five evaluators (A, 1.03 in step 1 and 0.63 in step 2, P < 0.001; B, 0.83 and 0.56, P < 0.001; C, 0.72 and 0.50, P < 0.001; D, 0.82 and 0.62, P < 0.001; E, 0.55 and 0.34, P < 0.001). This indicated that M‐NBI has an additive value for estimating the invasion depth of superficial esophageal SCCs.